Review on Future Trends of Digital Marketing: Exploring the Impact and Growth of Digital Marketing (Journal of Advances and Scholarly Researches in Allied Education, 2019)
New ways for influencing target customers has grown with the introduction of faster internet technologies. Regardless of its shape and size, digital marketing is becoming the integral part of any company. Digital marketing has changed the manner of services of companies, with the increasing demand of DM, now companies are working with existing and new customers as well. Paper highlights some key features of digital marketing like from historical background to its utilization presently, different kinds of internet marketing. The present study made an attempt to reveal the impact of digital marketing on customer purchase decision. This paper is an attempt to study the growth trend of digital marketing with the recent trends.